Eating disorders in adolescent and young adult males: prevalence, diagnosis, and treatment strategies - Limbers CA; Cohen LA; Gray BA (Dove Medical Press, 2018)
Christine A Limbers, L Adelyn Cohen, Bethany A Gray Department of Psychology and Neuroscience, Baylor University, Waco, TX, USA Abstract: Males have largely been underrepresented in the eating disorder (ED) peer-reviewed literature. The current review paper examines prevalence rates, ED symptom presentation, and assessment and treatment strategies relevant to adolescent and young adult males. Adolescent and young adult males often report a greater desire to be bigger and more muscular compared to their female counterparts. Due to concerns that contemporary ED assessment tools are over reliant on items that evaluate stereotypically feminine indicators of ED pathology, male-specific ED measures, such as the Eating Disorder Assessment for Men, have been developed. Further validation work is necessary to establish the psychometric properties of these male-specific measures, particularly in adolescent male populations. Attention to a heightened prevalence of comorbid substance abuse disorders and the role that competitive sports play in perpetuating ED pathology are two factors that have been identified as important in the treatment of adolescent and young adult males with EDs. Keywords: males, eating disorders, assessment, treatment, prevalence